Empowering Medical Students by Facilitating Cardiopulmonary Resuscitation Training for Their Peer - Hafizah Zainal Abidin; Juliza Jamaludin (Malaysian Journal of Science Health & Technology, 2024)
Cardiopulmonary Resuscitation (CPR) training is an essential component of medical education, equipping students with life-saving skills to respond effectively in emergencies. Following a CPR training program, this study investigates the impact of medical students’ knowledge and confidence levels as they facilitate hands-on CPR sessions for their peers. Through a review of literature and empirical analysis, this research elucidates the benefits of peer-assisted learning in CPR education. Results indicate a significant improvement in both knowledge and confidence levels among facilitators following the CPR training program. Overall, the findings highlight the invaluable role of medical student facilitators in enhancing CPR training outcomes and fostering a culture of peer support and empowerment within the medical community. This study underscores the significance of integrating peer-assisted learning strategies into CPR education programs, providing medical students with opportunities for both personal and professional growth. By leveraging the expertise and enthusiasm of medical student facilitators, educators can enhance the effectiveness and sustainability of CPR training initiatives, ultimately contributing to improved patient outcomes and community resilience in emergencies.